Implementasi Peraturan Gubernur No. 34 Tahun 2010 Tentang Uraian Tugas dan Fungsi Unit Pelaksana Teknis Dinas Pengelolaan Keuangan dan Asset Daerah Kabupaten Serang - Suharyono, Suharyono (Sawala : Jurnal Administrasi Negara, 2017)
Implementation Governor Rules Number 34 Year 2010 a bout on the Description of Duties and Functions of the Regional Technical Implementation Unit in the Region of Banten Province in Technical Implementation Unit of the Department of Management of Regional Assets and Assets of Serang regency Suharyono,  Regional autonomy provides local authorities to make the norm of about regional organizations. Peraturan Gubernur No. 34 Tahun 2010 on Duties and Functions of the Office of Technical Implementation Unit Banten Provincial structured as public policies that govern the work system UPT UPT organization in order to run effectively. The purpose of this study was to analyze the impact of public policy on the effectiveness of the organization at the Technical Implementation Unit Office of Financial Management and Asset Serang District. This research is using qualitative approach. The object of this research is the UPT Office of Financial Management and Asset Serang district, Banten Province. Based on the interview with the Head Unit, Head of Sub Division of Administration, staff and staff PKB and BBNKB Other revenues can be concluded that the public policy that t Peraturan Gubernur No. 34 Tahun 2010 on Duties and Functions of the Office of Technical Implementation Unit Banten Provincial UPT has been run by the Department of Finance and Asset Management Serang regency well. Order Unit Office of Financial Management and Asset Serang regency in implementing public policies impact on the ongoing activities of organiasi effectively.